An Investigation of the Impact of Organisational Structure on Organisational Performance - Nene, Sinqobile W; Pillay, Alan S (Financial Risk and Management Reviews, 2019)
Organisational structure is one of the core aspects that contribute to organisational performance. It can thus be said that it is the single most critical part of ensuring that the organization achieves its organisational objectives. This study examined the impact of organisational structure on the organisational performance of the Property Administration Services Department (PAS) within an organisation located at the Rosherville Industrial Area in Johannesburg South, South Africa. The study intended to give a practical perspective on the impact of a complex organisational structure on elements of personnel job satisfaction and departmental performance. The research instrument was designed to establish the elements that influence the composition of the organisational structure. Data analysis was done through descriptive and inferential statistics. The conclusion showed the inference between these elements and the actual aim of this study. The study did not directly compare the analysis of performance and organisational structure influence on it but rather aimed at establishing the general consensus by the participants on the likelihood of them accepting suggestions and recommendations of the study. It was evident that the organisational structure is ineffective. The ineffectiveness of the structure was observed to have been a contributing factor to the low job satisfaction levels within the participants. The context of the study identified staff morale as the main contributor to poor performance. Therefore, it could be concluded that since the organisational structure negatively impacted staff morale, it also inadvertently negatively affected the performance of the department.